Incorporation of bactericidal poly-acrylic acid modified copper iodide particles into adhesive resins. Issue 5 (May 2015) - Sabatini, Camila; Mennito, Anthony S.; Wolf, Bethany J.; Pashley, David H.; Renné, Walter G.
Abstract Objectives This study aimed to investigate incorporation of polyacrylic acid (PAA) coated copper iodide (CuI) nanoparticles into dental adhesives, and to evaluate for the first time, their antibacterial properties, bond strength and cytotoxicity. Methods PAA-CuI nanoparticles were synthesized and incorporated into commercially available adhesives Optibond XTR (1.0 mg/ml) and XP Bond (0.5 and 1.0 mg/ml). The antibacterial properties of experimental and control specimens were evaluated (n = 8), after ageing for 18 h or 1 year, against Streptococcus mutans (1 × 108 cells/ml). Bond strength to human dentine of the control and experimental adhesives was evaluated by shear bond strength (n = 10). For cytotoxicity evaluation, HGF cells were cultured with gingival fibroblast media and exposed to control and experimental adhesive blends (n = 3). An MTT cell viability assay was used to assess cell metabolic function. A one-way analysis of variance followed by Tukey's test was used for data analysis. Results Significantly greater antibacterial properties were demonstrated for PAA-CuI containing adhesives after ageing for 18 h or 1 year relative to all control groups. A reduction in Streptococcus mutans viable cell count of 99.99%, 99.99% and 79.65% was shown for XP Bond – 0.5 mg/ml, XP Bond – 1.0 mg/ml and Optibond XTR – 1.0 mg/ml PAA-CuI after ageing for 18 h, and 99.99% for both XP Bond – 0.5 mg/ml and XP Bond – 1.0 mg/ml PAA-CuI after ageing for 1 year. No significant variations in shear bond strength or cytotoxicity were detected between the experimental resins and their corresponding controls. Conclusions PAA-CuI nanoparticles are an effective additive to adhesive blends as it renders them antibacterial without adversely affecting their bond strength or cytotoxicity. Clinical significance The incorporation of PAA-coated copper iodide particles into adhesive resins renders the adhesive antibacterial to S. mutans for at least 1 year in vitro. This may prevent or delay bacterial invasion and the consequent development of caries lesions if the adhesive interface becomes defective.